Experimental Study on Mechanical Properties and Energy Dissipation of Gas Coal under Dynamic and Static Loads - Xiang Cheng; Guangming Zhao; Yingming Li; Xiangrui Meng; Qingyi Tu; Chunliang Dong (Advances in Civil Engineering)
In order to study the mechanical properties and energy dissipation of gas coal under dynamic and static loads, the static loading and impact tests of different strain rates were carried out by the testing systems of SZW-1000 microcomputer servo pressure tester and separated Hopkinson pressure bar (SHPB) for gas coal in the Panxie Coal Field in Huainan City. In the test, the influence laws of various loading patterns on mechanical properties, failure characteristics, and energy dissipation of gas coal sample were analyzed. The results showed that the stress-strain curve of coal gas under dynamic load had no micropore compaction stage compared with that under static load. Dynamic compressive strength, dynamic strength growth factor, mixed dynamic elasticity modulus, and dissipation energy were all highly correlated with strain rate, whereas energy dissipation rate was uncorrelated with strain rate. In addition, the gas coal sample with lower strain had small dissipated energy, and it developed a splitting failure mode. With the increase of strain rate, the dissipation energy increased and the crushing degree of gas coal intensified, finally presenting a compressive failure mode. Based on the comparison of dissipated energy densities of different gas coal samples, given the same dissipated energy density, the failure degree of sample under dynamic load was higher than that under static load.